Applying a Gendered Lens to the Stay and Defend or Leave Early Approach to Bushfire Safety. Issue 4 (23rd July 2018) - Reynolds, Benjamin; Tyler, Meagan
Abstract: This paper provides an historical and cultural context, from a feminist perspective, of the Prepare, Stay and Defend or Leave Early (PSDLE) bushfire safety policy, colloquially known as 'Stay or Go', in Australia. We examine the historical, cultural, and political factors that have devalued and marginalised women's experience and knowledge of bushfire preparedness and response. The central tenet of Stay or Go is that able bodied, prepared people should remain with their houses during a fire threat, best embodied by the common maxim 'people save houses and houses save people'. This approach has been routinely presented as evidence‐based policy but the argument presented here challenges the evidence base for the policy by applying a feminist analysis, through the application of a 'gendered lens'. This shows that an assumed masculine norm, at a number of different levels, has had a profound effect on the dominant readings of the available evidence about bushfire safety which has skewed bushfire safety policy and compromised the possibility of effective alternative responses. The PSDLE/Stay or Go policy is a prime example of the importance of applying critical feminist analyses to unsettle existing assumptions of policy development and implementation. Abstract : This paper provides an historical and cultural context, from a feminist perspective, of the Prepare, Stay and Defend or Leave Early bushfire safety policy in Australia. We examine the historical, cultural and political factors that have devalued and marginalized women's experience and knowledge of bushfire preparedness and response.